Stomaching Modern-day Ills - The Sun, Prakash Jayakumar (2008)
NOT many people are aware of it but the stomach is the root of many modem day ills. A healthy gastrointestinal tract is essential for overall wellbeing - a fact Bion3 went all out to reinforce during its health focused roadshows in Selangor, Kuala Lumpur and Penang recently.